Humanizing sustainable development through green spaces: a case study of Saudi cities - Mostafa, Ayman Mohamed; Alshahrani, Adnan (Frontiers in Sustainable Cities, 2024)
This research examines the significance of green areas in urban communities in contributing to quality of life and fostering sustainable development for Saudi cities, specifically desert cities. The quantitative method was adopted relying on municipal records and population data, specifically for public green areas such as parks and gardens. The analysis was conducted with reference to the City Prosperity Index (CPI) to ascertain the role of green spaces in urban livability and sustainability. The results revealed enormous disparities in per capita green space provision across Saudi cities. While the Northern Borders region contributed 21.082per capita, Jeddah contributed only 3.212 per capita. This observation stresses the immediate necessity to maximize urban greenery to augment quality of life and urban resilience. The results stress the vital importance of green spaces in advancing public health, supporting social cohesion, and promoting climate resilience. Moreover, the research highlights the importance of governmental programs, including the Saudi Green Initiative and the Humanization of Neighborhoods Initiative, that tend to solve these issues by promoting the use of drought tolerant plants and enhancing urban greening. The report ultimately presents key suggestions, including optimizing green space density, encouraging fair distribution, and raising people’s appreciation of the environmental and social values of green infrastructure. These actions must be taken to foster sustainable urban development and enhance the overall well-being of urban residents.